The Effect of Perceived Organizational Support on Employee Resistance to Change: A Study on Guilan Municipal Staff - Jabbarian, Jamal; Chegini, Mehrdad Goudarzvand (Journal of History Culture and Art Research, 2017)
The main objective of this study is to investigate the effect of perceived organizational support in the resistance to change among the official staff of Guilan municipalities. The study population includes all municipalities of the province of Guilan, which has 1631 official staff. The study reached 254 people, which is above the necessary population—224—for the study to reach a meaningful result. The study used stratified random sampling. In this study, a questionnaire, consists of four-parts, was used to collect data. The first part of the variable is related to organizational support that is derived from the research of Apodaca (2010); the second part of the questionnaire related to positive psychological capital variables derived from the research of Sapayaprapa (2013); the third part of the questionnaire related to identifying attitudes of employees regarding to change is derived from the research of Shea et al (2014); and the fourth part of the questionnaire related to the variable resistance to change that is derived from Giangreco (2002). The results of this study, the relationship between perceived organizational support and resistance to change is evident as follows: readiness for change, the relationship between positive psychological capital and the resistance to change and the relationship between perceived organizational support and mediates resistance to change. The negative correlation between readiness for change and resistance to change among government employees in Guilan municipalities.